EDUKASI HIPERTENSI DAN IDENTIFIKASI FAKTOR RISIKO PADA REMAJA SEBAGAI UPAYA PENCEGAHAN DINI PEMERLU PERAWATAN JANGKA PANJANG - Ni Kadek Sutini; Putu Inge Ruth Suantika; Ni Made Manik Elisa Putri; I Gede Putu Darma Suyasa; Ni Putu Kamaryati; Sri Dewi Megayanti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Hypertension remains a major public health issue in Indonesia. The 2018 Riskesdas reported that 34% of Indonesians suffer from hypertension, with 13.2% occurring in young people. Both genetic factors and unhealthy lifestyles are significant risk factors for hypertension among adolescents. These data indicate that adolescents are at high risk of developing hypertension. Hypertension is a serious condition that requires long-term care due to complications such as stroke, kidney failure, and heart disease. Providing education on hypertension and identifying its risk factors are among the key strategies for prevention in adolescents. This Community Service Program (PKM) aimed to provide information about hypertension and identify risk factors among adolescents. The activity was carried out with 50 students from SMA Negeri 1 Abiansemal, Badung Regency, Bali. The method used was PARE (Preparation, Action, Reflection, and Evaluation). The results of the program showed an increase in adolescents’ knowledge about hypertension after receiving education, with the Wilcoxon Signed Rank Test indicating a z-value of -6.122 and a p-value < 0.001. Identification of risk factors revealed that most adolescents practiced unhealthy lifestyles such as low physical activity, frequent consumption of fast food and fatty foods, insufficient intake of vegetables, caffeine consumption, and smoking. Although only a small proportion of adolescents had a family history of hypertension as the main risk factor, prevention efforts are still necessary through lifestyle modification